1988
DOI: 10.1042/bj2540895
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the aspartic proteinases from human erythrocyte membranes and gastric mucosa (slow-moving proteinase) as catalytically equivalent to cathepsin E

Abstract: Three aspartic proteinases with similar Mr values (approx. 80,000) but from distinct sources (human gastric mucosa, human erythrocyte membranes and rat spleen) were shown to have immunological cross-reactivity and comparable mobilities when subjected to polyacrylamide-gel electrophoresis under non-denaturing conditions. Kinetic parameters (kcat, Km and Ki) were determined for the interactions of the three enzymes with two synthetic chromogenic substrates and five inhibitors (naturally occurring and synthetic).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
4
45
0
Order By: Relevance
“…Values for k~a, were derived from Vma X = k,.,, " [E] where the active concentration of individual preparations of enzyme was determined by active site titration against pepstatin as described previously [18]. The protein inhibitor from Ascaris lumbricoides and the synthetic inhibitor H-77 described previously [4,7,17], were kindly provided by Dr. R.J. Peanasky, University of South Dakota, USA and Dr. P.A. Charlton (formerly) of Glaxo, Greenford, UK, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Values for k~a, were derived from Vma X = k,.,, " [E] where the active concentration of individual preparations of enzyme was determined by active site titration against pepstatin as described previously [18]. The protein inhibitor from Ascaris lumbricoides and the synthetic inhibitor H-77 described previously [4,7,17], were kindly provided by Dr. R.J. Peanasky, University of South Dakota, USA and Dr. P.A. Charlton (formerly) of Glaxo, Greenford, UK, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Proteolytic activity was measured against haemoglobin as substrate [14] in 0.17 M sodium citrate buffer, pH 3.1, when crude preparations needed to be evaluated; or utilising peptide substrates containing p-nitrophenylalanine (Nph) in the P~ position as a chromogenic reporter group [17] when purer enzyme samples were available. Kinetic analyses with two of these peptide substrates (generously provided by Dr. Ben M. Dunn, University of Florida, USA) were performed as described previously [4] except that the pH used was pH 3.1 at a final ionic strength of 0.1 M. Initial velocities were measured with at least six concentrations of each peptide substrate within an appropriate range in order to derive the kinetic constants, K, I1 and Vm~x. The estimated error for all measurements was always < 15%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum pH ofcathepsin E towards hemoglobin is 3-3.5, so its proteolytic activity and substrate speci- ficity were investigated previously only at acidic pHs [3,[12][13][14]. As far as cathepsin E can be active only at acidic pHs, its physiological roles in vivo would be highly restricted.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we have analyzed the inhibition of aspartic proteases by a 17 kD inhibitor known as pepsin inhibitor-3 (PI3), which was originally isolated from the nematode Ascaris suum that infects pigs and is closely related to A. lumbricoides that infects humans (21). Previous studies have found that PI3 is a tight binding inhibitor of pepsin, gastricsin (21), and cathepsin E (22)(23)(24).…”
mentioning
confidence: 99%